Downregulated lncRNA GAS5 and Upregulated miR-21 Lead to Epithelial–Mesenchymal Transition and Lung Metastasis of Osteosarcomas - Wang, Ying; Ren, Xue; Yuan, Ye; Yuan, Bao-Shan (Frontiers in Cell and Developmental Biology, 2021)
Lung is the primary site of osteosarcoma metastasis but the underlying genetic or epigenetic factors determining lung metastasis of osteosarcoma are unknown. In this study, we report the status of GAS5 (growth arrest specific 5) in lung metastatic osteosarcomas. GAS5 was generally downregulated in osteosarcoma patients (n=24), compared to the healthy controls (n=10) and even more so in the patients with lung metastatic disease (n=11), compared to the patients without metastasis (n=13). We also report a role of miR-21 in GAS5-mediated effects. Downregulation of GAS5 in hFOB 1.19 and U2OS osteosarcoma cells enhanced their migration and invasion, along with an upregulated epithelial-mesenchymal transition (EMT), as evidenced by downregulated E-Cadherin and upregulated Vimentin, ZEB1 and ZEB2. Downregulation of GAS5 also resulted in a significantly increased expression of miR-21. Moreover, downregulation of such elevated miR-21 was found to reverse the effects of GAS5 silencing. miR-21 was also found to be elevated in osteosarcoma patients with its levels particularly high in patients with lung metastasis. Our observations reveal a possible role of GAS5 and miR-21 in lung metastasis of osteosarcoma, presenting them as novel targets for therapy.